Rietveld structure analysis of keatite, a rare, metastable SiO2 polymorph - Grosskreuz Isabel; Marler Bernd (Zeitschrift für Kristallographie - New Crystal Structures)
O24Si12, tetragonal, P43212 (no. 96), a = 7.4462(1) Å, c = 8.5838(4) Å, V = 475.93(3) Å3, Z = 1, R(F) = 0.037, T = 293 K.